Salinity Gradient Energy : Technology Brief - Ruud, Kempener; Frank, Neumann (International Renewable Energy Agency IRENA, 2014)
This brief examines salinity gradient energy technologies, one of the key methods for tapping renewable energy from the world's oceans.
Keywords: Saline water conversion.; Saline water conversion -- Technological innovations.; elektronické knihy; electronic books